Echinopsis pachanoi "San Pedro female" rizospheric mush-rooms and their potential as growth promoters in Zea mays L. under saline stress - Uypan Farro, Carlos Jair (2021)
Objectives: To determine the potential of Echinopsis pachanoi curly fungi "San Pedro Female", as growth promoters in Zea mays L. "corn" under saline stress. Materials and methods: Descriptive cross-sectional study. The fungi were isolated in dextrose potato agar (PDA) and phenotypically identified. The activity of the enzyme 1- aminocyclopropane carboxylate (ACC) deaminase, the production of natures, solubilization of tricalcium phosphate was investigated and the effect on the development of maize, on a saline soil (CE-8,213 dSm-1), under greenhouse conditions. Results: Ten genera of filamentous fungi were identified predominantly Aspergillus spp. (35.92%), Trichoderma spp. (17,96%) and Penicillium spp. (16,16%). The four fungi of the selected genera Trichoderma and Penicillium produced natures, soubilized phosphate and increased the values of maize development parameters, reaching 100.98% in the height; 23.0% in the number of leaves; 47.33% on root length and 106.67% on root weight. Conclusions: The beneficial potential of Trichoderma spp was demonstrated. and Penicillium spp. in corn under salinity.